Evaluation of a taurine containing amino acid solution in parenteral nutrition. Issue 1 (January 1991) - Thornton, L; Griffin, E
Abstract : Vaminolact, an amino acid solution containing taurine, was given to 15 sick newborn babies. They were compared with a group of 10 babies who received a solution that did not contain taurine (Vamin glucose). Efficacy and safety were evaluated by monitoring plasma amino acid patterns, growth patterns, nitrogen balance, and biochemical and haematological profiles. No serious abnormalities in amino acid concentrations were found. After an initial fall the taurine concentration recovered more rapidly in those receiving the taurine supplement, though this difference was not significant. Phenylalanine concentrations were within the reference range in the group receiving Vaminolact, and were significantly lower than in the group receiving Vamin glucose. Metabolic acidosis, which occurred in several subjects in each group, was not a serious problem. Liver function tests remained satisfactory. Nitrogen retention was greater among those receiving Vaminolact than in the control group. Vaminolact is a safe and effective amino acid solution for use in critically ill babies.